Origin and seed coat color differently affect the concentrations of metabolites and antioxidant activities in soybean (Glycine max (L.) Merrill) seeds. (1st July 2022) - Desta, Kebede Taye; Hur, On Sook; Lee, Sukyeung; Yoon, Hyemyeong; Shin, Myoung-Jae; Yi, Jungyoon; Lee, Yoonjung; Ro, Na Young; Wang, Xiaohan; Choi, Yu-Mi
Graphical abstract: Highlights: Soybean seeds of diverse origins and seed coat colors were cultivated in Korea. The contents of several metabolites and antioxidant activities were analyzed. Metabolite contents and antioxidant activities significantly varied ( p  < 0.05). Korean soybeans displayed the highest average total isoflavone content. Black soybeans were dominant in terms of TPC level and antioxidant activities. Abstract: In this study, 54 soybean germplasms of different seed coat colors originated from America, China, Japan, and Korea were cultivated in Korea and analyzed for the contents of total oil, total protein, total phenolic, five fatty acids, and five isoflavones, and antioxidant activities using three assays. The soybeans showed significant variations ( p  < 0.05) of metabolite contents and antioxidant activities. Origin and seed coat color exhibited a slight or insignificant effect on total protein and total oil contents. In contrast, origin and seed coat color significantly affected the concentration of individual and total isoflavones, and total phenolics, with few exceptions. Whereas fatty acids were significantly affected by origin, seed coat color provided better information regarding the variations in antioxidant capacities. Together, multivariate and correlation analyses revealed important associations between biosynthetically-related metabolites. In general, origin and seed coat color differently influenced the concentration of different classes of metabolites and antioxidant activities.